What Is the Best Surgical Treatment of Pouch-Vaginal Fistulas?. Issue 5 (May 2019) - Sapci, Ipek; Akeel, Nouf; DeLeon, Michelle F.; Stocchi, Luca; Hull, Tracy
Abstract : BACKGROUND: Pouch-vaginal fistula is a debilitating condition with no single best surgical treatment described. Closure of these fistulas can be incredibly difficult, and transanal, transabdominal, and transvaginal approaches have been reported with varying success rates. Recurrence is a major problem and could eventually result in repeat redo pouch or permanent diversion. OBJECTIVE: The aim of our study was to investigate healing rates for procedures done for pouch-vaginal fistula closure. DESIGN: This is a retrospective analysis of a prospectively maintained database complemented by chart review. SETTINGS: This study reports data of a tertiary referral center. PATIENTS: Patients who underwent surgery for pouch-vaginal fistula from 2010 to 2017 were identified. Patients who underwent surgery with intent to close the fistula were included, and patients who had inadequate follow-up to verify fistula status were excluded. INTERVENTIONS: Patients included underwent surgery to close pouch-vaginal fistula. MAIN OUTCOME MEASURES: Success of the surgery was the main outcome measure. Success was defined as procedures with no reported recurrence of fistula on last follow-up. RESULTS: A total of 70 patients underwent surgery with an intent to close the pouch-vaginal fistula, 65 of whom had undergone index IPAA for ulcerative colitis, but 13 of these patients later had the diagnosis changed to Crohn's disease. Thirty-nine patients (56%) had a fistula originating from anal transition zone to dentate line to the vagina (not at the pouch anastomosis). In the total group of 70 patients, our successful closure rate was 39 (56%) of 70. Procedures with the highest success rates were perineal ileal pouch advancement flap and redo IPAA (61% and 69%). LIMITATIONS: The retrospective nature and small number of cases are the limitations of the study. CONCLUSIONS: Although numerous procedures may be used in an attempt to close pouch-vaginal fistula, pouch advancement and redo pouch were the most successful in closing the fistula. See Video Abstract at http://links.lww.com/DCR/A841 .